(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Laparoscopic surgery has emerged as a promising alternative to traditional open repair for perforated peptic ulcer (PPU). Objective: This retrospective comparative study aimed to evaluate the clinical outcomes of laparoscopic and open surgical repairs in a tertiary care setting. Methods: Eighty-two patients with perforated gastric or duodenal ulcers were included, with 32 undergoing laparoscopic surgery (Group I) and 25 undergoing open surgery (Group II) based on stringent inclusion criteria. Laparoscopic repair involved a diagnostic laparoscopy, ulcer closure with single-layer sutures, and omentopexy, which was performed. Open surgery was performed through midline laparotomy with a similar ulcer closure. Postoperatively, both groups received antibiotics, pain relief, and early mobilization therapy. Results: Group I had a significantly shorter hospital stay (3.8 ± 0.38 days vs. 6.9 ± 0.75 days, P < 0.001) and quicker oral intake resumption (1.6 ± 0.5 days vs. 2.8 ± 0.8 days, P = 0.002) than Group II. The incidence of post-operative complications was lower in Group I (3.1% vs. 12.0%, P = 0.03). No surgical site infections, pneumonia, reoperations, or mortality occurred in Group I. Conclusion: These findings suggest that laparoscopic repair is a safe and effective alternative to open surgery for PPUs in selected patients, offering shorter hospital stays, fewer complications, and faster recovery. However, careful patient selection based on perforation size, location, presentation time, and comorbidities is crucial for successful outcomes. Further prospective multicenter studies are needed to confirm these results and establish guidelines for wider clinical applications, particularly in resource-limited settings.